Why Pay Attention to You? The Role of Moderation Effects on the Power-Attention Relationship - Tarr, Emily K.; Kohles, Jeffrey C. (Journal of Organizational Psychology, 2019)
Stories in today’s society focus poor relationships between leaders or those in high power positions and people lower in power, which may be explained by a pattern found in the literature demonstrating a negative relationship between power and attention to others. We contend that this relationship may have boundary conditions, and this paper proposes and tests such moderators. We propose moderators that will increase the attention of high-power people, and others that will decrease the attention of low-power people. Results from longitudinal data support some moderators for powerholders, the moderators for low-power individuals work in the opposite direction as hypothesized.